Manajemen Edupreneurship untuk Meningkatkan Kinerja dan Keberlanjutan Pembiayaan di SMK Negeri 1 Glagah Banyuwangi - Misbahul Arifin; Abdul Majid; Muhammad Zaki Maulana; Abdullah (CV Edujavare Publishing, 2024)
This research is motivated by the challenges of sustainable education financing in vocational high schools, which demand managerial innovation based on educational entrepreneurship. Edupreneurship is viewed as a strategic approach oriented not only toward strengthening student competencies but also toward improving school performance and the sustainability of education financing. This study aims to examine in depth how edupreneurship management is implemented to improve performance and financial sustainability at SMK Negeri 1 Glagah Banyuwangi. The research employed a qualitative case study approach. Data were collected through in-depth interviews, participant observation, and documentation studies, then analyzed using interactive qualitative data analysis techniques that included data reduction, data presentation, and conclusion drawing. The results indicate that edupreneurship management integrated with practical learning, production units, and teaching factories can improve school performance while simultaneously strengthening sources of sustainable education financing. Edupreneurship functions as a mutually reinforcing pedagogical and economic instrument within the school management system. The implications of this research emphasize the importance of strengthening institutional policies, school leadership, and curriculum integration as prerequisites for the success of edupreneurship in supporting sustainable vocational education financing.